Comparison of player's center of mass movement between high and low impact positions in tennis forehand stroke - Lin, C. Y.; Lo, K. C.; Lin, H. T.; Wang, L. H. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
During the tennis forehand stroke, the displacement of body center of mass (COM) changes with the body movement. The COM movement influences the recovery from one stroke to the next. Therefore, the purpose of this study is to investigate the differences of COM movement and joint kinematics between high and low-impact positions on different skilled players. This study adopted a 3-D motion analysis system for recording and tracing the advanced (n = 5; level 3-4) and intermediate (n = 7; level 5-6) athletes' motion of whole body during high and low-impact positions in tennis forehand stroke. The results showed that significant difference was not found between both impact positions and level groups in ball velocity. Advanced group showed greater anterior/posterior displacement than the intermediate group in low-impact position that increased the kinetic energy.